Case for diagnosis - Rogerio Nabor Kondo; Rubens Pontello Junior; Ricardo Pontello; Jefferson Crespigio (Sociedade Brasileira de Dermatologia, 2014)
Subcutaneous phaeohyphomycosis is an infection caused by dematiaceous fungi which mainly affects immunosuppressed patients. We report a case of subcutaneous phaeohyphomycosis on the back of the left hand in a kidney transplant patient who had been taking prednisone, tacrolimus, and azathioprine daily for 3 years.